Nest Building Ability and Nest Characteristic of Pre-release Bornean Orangutan (Pongo pygmaeus) in Jerora Forest School, Sintang Orangutan Center, West Kalimantan - Hapsari Indriastuti; Luthfiralda Sjahfirdi; Tatang Mitra Setia (Postgraduate, University of Mataram, 2025)
Rescue, rehabilitation, and release is one of the strategies for orangutan conservation. Jerora Forest School, Sintang Orangutan Center, West Kalimantan, is a place to rehabilitate orangutan. One of the criteria for orangutan to be ready for release is the ability to build nests. The objective of this study was to analyze the nest building ability and nest characteristic preferences of four pre-release female bornean orangutans (Jamilah, Penai, Joss, and Bondan) in Jerora Forest School. Data was collected in November 2024 to January 2025 using the focal animal sampling, ad libitum sampling, and continuous recording methods. Three out of four female pre-release bornean orangutans (Jamilah, Joss, and Bondan) are categorized as moderate on their ability to build nest, while Penai is less capable. Nest trees used by the juvenile orangutan are more diverse than the ones used by the adult orangutan. The characteristics of the nests used by the research subjects were relatively similar across each age group. Nest trees used by the juvenile orangutans are more diverse than the ones used by the adult orangutans. Based on the nest building observation, Jamilah, Joss, and Bondan are ready to be released, while Penai is not ready to be released yet.